(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
The study explained the role of the Siliwangi Division in outside area of its defence base. Siliwangi Division which has a territorial responsibility of West Java must struggle to maintain the independence of the Republic of Indonesia that almost gone. This study aimed to elaborate Siliwangi Division’s struggle, particularly in defending the state from internal threats. The method used was a historical method. As a result, this research found that Siliwangi Division had succeeded to quell PKI’s rebellion at Madiun in 1948 that threatened the continuance of the Republic of Indonesia. Siliwangi Division also took part in quelled the rebels, because at that time most divisions in Central and East Java were assigned to guard of the Republic of Indonesia’s border. PKI’s rebellion was an internal threat that threatens to the continuance of the Republic of Indonesia. Siliwangi Division with some troops around Yogyakarta, Central and East Java, was employed to execute quell operation against the rebellions. Kian Santang Battalion under the leadership of Major Sambas Atmadinata of the Siliwangi Division became the first troop that retake Madiun. Meanwhile, Kala Hitam Battalion led by Major Kemal Idris and Suryakencana Battalion led by Major R.A Kosasih were involved in the final battle and succeed arrested the prominent rebel figures.